Pacific Islands Families Study: Patterns of Intimate Partner Violence Among Pacific Mothers - Paterson, Janis (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is a widespread social problem affecting all populations regardless of gender, race, and socioeconomic status. The aims of this study were to examine (a) patterns of IPV among Pacific women living in New Zealand and (b) the risk and protective factors associated with IPV perpetration and victimization. As part of the longitudinal Pacific Islands Families (PIF) Study, maternal interviews, which included reports about IPV, acculturation, and sociodemographic characteristics, were administered at phases 6 weeks, 2, 6, 11, and 14 years postpartum. Age had a significant effect on perpetration of both minor and severe perpetration of IPV, and on being a victim of minor IPV. However, no significant effect was found for severe victimization. Cultural alignment also had a significant effect on perpetration of IPV with Pacific mothers who were strongly aligned to their traditional Pacific culture being significantly less likely to report minor or severe IPV perpetration compared with Pacific mothers who were closely aligned to western culture. Single mothers reported significantly more minor victimization, and those mothers who were more highly educated and were in a higher income bracket were significantly less likely to report severe physical IPV victimization. These findings can inform the timing and targeting of culturally appropriate violence prevention efforts in adolescence and young adulthood that focus on the development of healthy intimate partner relationships and effective methods of conflict resolution.